The Hijab Transformed: A Shifting Social Identity in Bauman's Liquid Modernity (Jurnal Sosiologi Reflektif, 2024)
The hijab, traditionally seen as a religious symbol in Islam, has undergone significant transformations in modern society, shifting its role from a marker of religious modesty to a dynamic symbol of social identity. Global cultural shifts, media representations, and the tension between traditional values and contemporary aspirations influence this transformation. The study explores the evolving meanings and functions of the hijab as a social identity in the context of Bauman's theory of liquid modernity. This research employs a qualitative literature review methodology to examine 40 peer-reviewed articles from both international and national journals. A content analysis approach is utilized to identify recurring themes and patterns in the hijab’s depiction as a social symbol across diverse cultural and social landscapes. The findings indicate that in the era of liquid modernity, the hijab symbolizes a fragmentation of its traditional meanings, shaped by forces like globalization, consumerism, and individualization. Although it continues to signify religious identity, the hijab also represents modernity, resistance, and commodification. Social media plays a crucial role in this transformation, offering a platform for Muslim women to reinterpret the hijab as both a personal and communal statement. This study highlights the hijab’s transformation into a fluid and multifaceted symbol of identity in a rapidly evolving global context.Jilbab, yang secara tradisional dipandang sebagai simbol religius dalam Islam, telah mengalami transformasi yang signifikan dalam masyarakat modern, bergeser dari peran sebagai penanda religius menjadi simbol identitas sosial yang dinamis. Transformasi ini dipengaruhi oleh pergeseran budaya global, representasi media, serta ketegangan antara nilai-nilai tradisional dan aspirasi kontemporer. Penelitian ini bertujuan untuk mengeksplorasi evolusi perubahan makna dan fungsi jilbab sebagai identitas sosial dalam konteks teori modernitas cair Bauman. Dengan menggunakan metode kualitatif berupa studi literatur, penelitian ini menganalisis 40 artikel jurnal bereputasi internasional dan nasional. Analisis konten digunakan untuk mengidentifikasi tema dan pola yang berulang terkait representasi jilbab sebagai identitas sosial di berbagai konteks budaya dan sosial. Hasil penelitian menunjukkan bahwa jilbab dalam era modernitas cair mencerminkan fragmentasi makna, yang dipengaruhi oleh globalisasi, konsumerisme, dan individualisasi. Meskipun tetap menjadi penanda identitas religius, jilbab kini juga berfungsi sebagai pernyataan modernitas, resistensi, dan komodifikasi. Media sosial memainkan peran penting dalam transformasi ini, menjadi platform bagi perempuan Muslim untuk mereformulasi jilbab sebagai ekspresi pribadi dan komunal. Studi ini menegaskan bahwa jilbab tidak lagi menjadi simbol yang statis, melainkan representasi identitas yang cair dan multifaset dalam dunia yang terus berubah.